The Effect of The Modified Snakes and Ladders Game on the Knowledge of School-Age Children in Choosing Healthy Snacks in West Java Indonesia - Wahyuni, Sri; Putri, Delia; Heni (International Journal of Applied Research and Sustainable Sciences, 2024)
Healthy snacks are nutritious snacks and do not contain dangerous substances. Many children, especially those in elementary schools, don't know about it, so they often become victims of snack poisoning at school. One of the events to provide health education to elementary school children is through modified snakes and ladders. This research aims to determine the effect of the modified snakes and ladders game on children's knowledge in choosing healthy snacks. This research uses quantitative methods with a quasi-experimental research design using a one group pretest-posttest design approach. with a total sample of 79 school age children. Based on the results of the research and discussion, it can be concluded that there is an influence of the modified snakes and ladders game on school children's knowledge in choosing healthy snacks with a value of p=0.000 <0.05. It is hoped that this research can provide knowledge to students and can also be used by teaching staff as a source of information that can help in improving healthy snacks. It is hoped that this research can add information and references for future researchers.